2014
DOI: 10.1080/11263504.2014.983578
|View full text |Cite
|
Sign up to set email alerts
|

On the identity of aCentaureapopulation on Procida Island, Italy:Centaurea corensisrediscovered

Abstract: The discovery on the Island Procida (Gulf of Naples, off the Italian west coast) of a Centaurea population similar to C. corensis, a narrow-range Sardinian endemic hitherto known only from one single locality in Sardinia, is here presented. The identification of the two populations as C. corensis is confirmed by morphological comparison and morphometric analysis, chromosome counts, and nrDNA sequence data. A recent origin of the species through polyploidization is hypothesized. Finally, the possibility that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
4
9
0
Order By: Relevance
“…Besides the three lineages formed by the most widespread endemic Centaurea from Sardinia, a fourth lineage, which is difficult to interpret, has to be considered: the C. corensis lineage (Fig 1). Previous studies have suggested that C. corensis is a tetraploid hybrid originating on Procida Island (Naples) that was carried to Sardinia by anthropic dispersion [37]. The hypothesis of a long distance, perhaps anthropic, dispersal is supported by our results because C. corensis from Sardinia presents an exclusive haplotype (yellow haplotype; Fig 1) that is not present in other species from Sardinia and is not derived from other haplotypes present on the island.…”
Section: Evolutionary Lineages On Islandssupporting
confidence: 83%
See 1 more Smart Citation
“…Besides the three lineages formed by the most widespread endemic Centaurea from Sardinia, a fourth lineage, which is difficult to interpret, has to be considered: the C. corensis lineage (Fig 1). Previous studies have suggested that C. corensis is a tetraploid hybrid originating on Procida Island (Naples) that was carried to Sardinia by anthropic dispersion [37]. The hypothesis of a long distance, perhaps anthropic, dispersal is supported by our results because C. corensis from Sardinia presents an exclusive haplotype (yellow haplotype; Fig 1) that is not present in other species from Sardinia and is not derived from other haplotypes present on the island.…”
Section: Evolutionary Lineages On Islandssupporting
confidence: 83%
“…Centaurea corensis is a perennial tetraploid (2n = 36 [37]) with a woody base, leaves in a basal rosette, white to pale pink capitula, and membranaceous bract appendages. The species grows only at one site in northwestern Sardinia and is morphologically similar to the C. deusta Ten.…”
Section: Introductionmentioning
confidence: 99%
“…All the other diagnostic features completely concur with C. corensis: ovate-cylindrical heads of medium size (within the C. deusta group), bracts greenish, appendage with a pale or silvery spot and rounded widely scarious margins, obtuse-rounded, muticous or with a short mucro (the upper ones), flower white rarely pinkish shaded, short pappus ( Figure 1). The occurrence of the taxon on the mainland better supports the hypothesis by Hilpold et al (2015), about the introduction into Sardinia by maritime transportation of volcanic rocks, as exchange of materials with Sardinia is well documented from the Phlaegrean Fields (Terracciano, 1917), but not from Procida island.…”
supporting
confidence: 79%
“…Sardinian Centaurea species show genetic relations with both eastern and western Mediterranean clades within the genus, and are more closely related to Italian taxa (Hilpold et al 2015). Centaurea filiformis is an endemic species, exclusively found in central-eastern Sardinia (Fig.…”
Section: Study Species and Sitesmentioning
confidence: 99%
“…Both factors conditioned the distribution of many plant species, which are now rare and confined to narrow ranges, often with scattered, isolated and small populations (Thompson 2005). Particular attention has recently been given to the evolution in space and time of population patches of Mediterranean plants (Garc ıa 2003(Garc ıa , 2008Garc ıa et al 2010;Budroni et al 2011Budroni et al , 2014Pisanu et al 2012), which are increasingly considered interesting subjects for evolutionary studies (Fern andez-Mazuecos et al 2014;Mameli et al 2014;Hilpold et al 2015).…”
Section: Introductionmentioning
confidence: 99%